New therapeutics for the treatment of glycosphingolipid lysosomal storage diseases. - Butters, T; Dwek, R; Platt, F (2003)
Glycosphingolipid lysosomal storage diseases are a small but challenging group of human disorders to treat. Although these appear to be monogenic disorders where the catalytic activity of enzymes in glycosphingolipid catabolism is impaired, the presentation and severity of disease is heterogeneous. Treatment is often restricted to palliative care, but in some disorders enzyme replacement does offer a significant clinical improvement of disease severity. An alternative therapeutic approach termed "substrate deprivation" or "substrate reduction therapy" (SRT) aims to reduce cellular glycosphingolipid biosynthesis to match the impairment in catalytic activity seen in lysosomal storage disorders. N-Alkylated imino sugars are nitrogen containing polyhydroxylated heterocycles that have inhibitory activity against the first enzyme in the pathway for glucosylating sphingolipid in eukaryotic cells, ceramide-specific glucosyltransferase. The use of N-alkylated imino sugars to establish SRT as an alternative therapeutic strategy is described in cell culture and gene knockout mouse disease models. One imino sugar, N-butyl-DNJ (NB-DNJ) has been used in clinical trials for type 1 Gaucher disease and has shown to be an effective and safe therapy for this disorder. The results of these trials and the prospects of improvement to the design of imino sugar compounds for treating Gaucher and other glycosphingolipid lysosomal storage disorders will be discussed.